Postawy producentów rolnych wobec metod produkcji rolnej przyjaznych środowisku - Pondel, Hanna (The Farmers Stances Toward the Environment Friendly Methods of Agricultural Production, 2006)
The article presents the attitude of farmers from Wielkopolska towards the production methods which are environment-friendly. According to the results of poll research, the farmers are not specially interested in ecological production methods. At the same time, ecological agriculture is the best known concept to farmers from among concepts which characterize environment-friendly production methods in agriculture.For entities which function in organic agriculture sphere the assistance is very important, because the ecological aim is competitive towards economic aim. It is very difficult to achieve both on a high level.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 242-247